2013
DOI: 10.1039/c3cc43540g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and specific sensing of gallic acid with a photoelectrochemical platform based on polyaniline–reduced graphene oxide–TiO2

Abstract: A novel photoelectrochemical sensor has been designed with polyaniline-reduced graphene oxide-titanium dioxide, which was further applied to sense gallic acid and exhibited extraordinary rapid response, high sensitivity and excellent anti-inference. Meanwhile, the mechanism has been elaborately explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…Concerned on such a technique, the essential requirement should be the accurate potential control as well as the favorable photocurrent response stability at every applied potential. Our previous research showed that the three-EPCS can well meet these criterions during the assay of antioxidant capacity (Ma et al, 2014;Ma et al, 2013;L. Wang et al, 2014;W.…”
Section: Resultsmentioning
confidence: 99%
“…Concerned on such a technique, the essential requirement should be the accurate potential control as well as the favorable photocurrent response stability at every applied potential. Our previous research showed that the three-EPCS can well meet these criterions during the assay of antioxidant capacity (Ma et al, 2014;Ma et al, 2013;L. Wang et al, 2014;W.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene/ TiO 2 nanocomposites were prepared by the hydrothermal process. Here graphene was reduced from graphene oxide [21,5], later TiO 2 nanoparticles were deposited on the graphene sheet with glucose as the facet controlling agent [21]. For the synthesis of TiO 2 nanofiber, it should be added with some specific polymer.…”
Section: E Modification Processmentioning
confidence: 99%
“…Based on its synthesis and properties, many other reviews and reports have been done. Those researches has been done with the promising chemical and physical properties which includes photoelectric activity, large surface area, high stability [1], adsorption edge energy, efficient separation of the charge carriers, crystallite size [2], high sensitivity, selectivity in the field of photo electrochemistry detection [3], high reactivity under ultraviolet light (<387 nm) [4], biological inert nature and high electronic mobility [5].…”
Section: Introductionmentioning
confidence: 99%
“…Niu's group developed antioxidant test methods based on quenching photocatalytic generated species (e.g., positive holes and ROS) [11][12][13] . On the basis of this, we established a kinetic model for this phtoelectrochemical detection technique for antioxidant test.…”
Section: +mentioning
confidence: 99%